Analysis of recruiting in Ukraine - Shpakovich, Ekaterina; Bozhok, Natalia (My University, 2014)
The phenomenon of “recruiting” is analyzed in the paper. The main aspects of “recruiting” are considered in general and the process of it formation is defined in Ukraine.
Keywords: recruiting companies; recruiting; applicant; рекрутингові компанії; рекрутинг; претендент; кафедра ділової іноземної мови та міжнародної комунікації